Preexercise static stretching effect on leaping performance in elite rhythmic gymnasts - Di Cagno, A.; Baldari, C.; Battaglia, C.; Gallotta, M. C.; Videira, M.; Piazza, M.; Guidetti, L. (The Journal of Strength and Conditioning Research, 2010)
The aim of this study was to examine the acute effects of static stretching (SS) on technical leaps performance in rhythmic gymnastics. Thirty-eight gymnasts (age 14.13 ± 3.2 years), competing at the international and national levels, performed vertical jumps (squat jump, countermovement jump, hopping test [HT]) and technical leaps (split leap with leg stretched [SL], split leap with ring [RG], split leap with back bend of the trunk [BBT]) assessed in 2 different conditions: after SS and after their usual typical warm-up (TWU) as control conditions. Jumps and leaps flight time (FT) and ground contact time (GCT) parameters were evaluated by OptoJump. Leap performance was simultaneously evaluated by scores awarded by judges. For each dependent variable, the effect of warm-up condition (TWU and SS) was examined by a paired-sample t-test. A multiple regression analysis determined the amount of variance in judges' scores from the FT and GCT variables. Results revealed that vertical jumps FT was not affected by SS warm-up. Ground contact time of HT significantly increased after SS warm-up (p < 0.01). Static stretching reduced significantly (p < 0.01) the technical leap FT (decrements: SL = 7.1%, RG = 7.2%, and BBT = 6.4%). The results showed no significant effects of SS on technical leaps GCT. Static stretching significantly reduced (p < 0.001) the scores awarded by the judges. The FT was the main predictor of scores of the 3 technical leaps accounting for 9-30% of variance in both warm-up conditions. This study suggests that SS before leaping performance may negatively affect rhythmic gymnastics judges' evaluation.